(untitled) (International Journal of Engineering and Computer Science, 2018)
This paper deals with issues, which network designers, would have to deal with once IPV6, which is the layer 3 Internet Protocol of the future comes into mass existence. IPV6 will have compatibility issues with most of the existing routing protocols especially with Border Gateway Protocol (BGPV4), which is a layer 7 protocol on which the backbone of the Internet runs. BGP Version 4 is an interdomain routing protocol. The primary function of BGP is to provide and exchange network reachability information between Autonomous Systems (AS).